Divergent sustainability profiles of molnupiravir synthesis routes are governed by solvent use and process design - Zhengyun Chen; Justin Z. Lian; Haozhou Huang; Hengyi Zhu; Lynda Thubelihle Kanye; Mateng Chen; Zhihao Zhang; Boxin Liu; Jiawei Zhang; Ajaz Ahmed; Valerio Barbarossa; Stefano Cucurachi; et al. (Proceedings of the National Academy of Sciences, 2025)
This study presents a comparative cradle-to-gate environmental and economic evaluation of nine synthetic routes for Molnupiravir (EIDD-2801), a broad-spectrum antiviral drug. Integrating Life Cycle Assessment (LCA) with Life Cycle Costing (LCC), we quantified the environmental impacts alongside capital and operational costs, net present costs, and break-even prices of each route. The results reveal significant variation across the schemes, with Schemes #1 and #2 exhibiting the highest impacts and costs due to intensive use of chloroform and diethyl ether, while Scheme #8 demonstrated the lowest impacts and costs, benefitting from higher batch output, greener solvents, and process intensification. Scenario analyses showed that solvent recovery improves sustainability only when high recovery rates are combined with clean electricity; otherwise, the additional energy demand may offset benefits. Scale-up analysis confirmed that higher production scales substantially reduce per-gram impacts and costs, supporting economies of scale. These findings highlight the critical role of solvent management, energy sourcing, the use of sustainability assessment at the earliest stages of innovation, and process design in aligning green chemistry with economic viability. The proposed integrated LCA-LCC framework provides transferable insights to guide sustainable pharmaceutical manufacturing and supports the development of evidence-based policy for greener antiviral drug production.